Q: -10x plus 3 equals -x plus 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7x+3=10x-9(shift +3 & 10x) 7x-10x=-9-3(signs changed) -3x=-12(divide both sides by -3) x=4

x2 + 10x + 21 = (x + 3)(x + 7)

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

x=3

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

Related questions

10x + 3 = 15 10x = 15 - 3 10x = 12 x = 1.2

-10x-6 = -12 -10x = -12+6 -10x = -6 x = 3/5

7x+3=10x-9(shift +3 & 10x) 7x-10x=-9-3(signs changed) -3x=-12(divide both sides by -3) x=4

x2 + 10x + 21 = (x + 3)(x + 7)

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

x=3

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

2x-3 = 21+10x 2x-10x = 21+3 -8x = 24 x = -3

It is: x = 1.2

10x+7=(-3) 10x=(-10) x=(-1)ans

6x - 3x = 5x - 10x + 12 6x - 3x - 5x + 10x = 12 8x = 12 8x/8 = 12/8 x = 12/8 = 3/2 x = 1.5

-2(5x+3)-2x<-3(2x-4)+2